Evaluation of Nutritional and Phytochemical Properties of Dried Soursop Seeds - Odunayo, Olabinjo, Oyebola (Canadian Journal of Agriculture and Crops, 2020)
Utilization of fruits that possess a large range of medicinal and health benefit is limited due to their fast rate deterioration especially in developing countries. The research study methods of drying as means of preserving seeds of soursop and its effects on its chemical constituents. The samples were dried in the open sun and oven (30- 60º C). The dryer reduces the moisture content from the fresh seed from 42.6% (w.b) between 14.61% (w.b.) for open sun and 19.72% at 30ºC and 13.75% (wb) at 60ºC for oven drying. Soursop seeds had an increase in value from fresh to dried for the followings; ash, fat, fibre, alkaloid, total phenolic, phylate and flavonoid content. There is reduction in value of soursop from fresh to dried for moisture, crude protein, carbohydrate, tannin and tritatable content. Oven at drying temperature of 40ºC had the best result in terms of nutritional and Phytochemicals constituents, which provides the health enhancing effects of the soursop seeds. The result is useful for farmers, researchers, and processors in agro processing industry in designing a reliable machine for processing soursop seeds which will boost production of soursop in Nigeria.